2020
DOI: 10.1007/s11469-020-00321-0
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Placebo: The Role of Expectations and Social Influence

Abstract: The placebo effect is frequently present in our lives when an expectation, associated with any psychoactive material, leads to subjective and physiological changes. The present work studies the role of expectancies associated with ethanol/alcohol in changes to the subjective state. In experimental situations, we examine how these expectations—with or without social influences—affect participants when consuming alcoholic, pseudo-alcoholic, or non-alcoholic cocktails. Psychological and physical changes can, to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…Alcohol consumption often occurs in social settings (e.g., with friends at a party) and effects of alcohol may differ depending on whether it is consumed individually or in a social setting. Similar contextual influences have been found for placebo effects, which can be different in individual and social settings (Bodnár et al, 2020). Thus, our lab findings may not be representative of the effects of alcohol and alcohol-related beliefs in general if their influence on moral judgments depends on the context.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Alcohol consumption often occurs in social settings (e.g., with friends at a party) and effects of alcohol may differ depending on whether it is consumed individually or in a social setting. Similar contextual influences have been found for placebo effects, which can be different in individual and social settings (Bodnár et al, 2020). Thus, our lab findings may not be representative of the effects of alcohol and alcohol-related beliefs in general if their influence on moral judgments depends on the context.…”
Section: Discussionsupporting
confidence: 60%
“…Second, only one of the three studies (Francis et al, 2019) included a placebo condition in which participants believed they were consuming alcohol without actually consuming alcohol. Placebo conditions are essential in this line of research to distinguish actual effects of alcohol from effects of people’s naïve beliefs about the influence of alcohol (Bodnár et al, 2020). In the context of moral judgments, it is also possible that people believe that being intoxicated gives them a license to make more pro-sacrificial judgments, even when alcohol itself has no causal effect on moral judgments.…”
Section: The Current Researchmentioning
confidence: 99%
“…Second, not all our participants believed they were in a placebo condition. It is quite hard to convince people that they are drunk because the experience of alcohol intoxication is quite common, and many challenges with using a placebo in alcohol studies have previously been identified (Bodnár et al, 2021). However, it must be noted that the self-assessments in the group that had actually consumed alcohol did not differ significantly from those of the two other groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, if this is not feasible, studies interested in determining the individual impact of alcohol's expectancy and pharmacological effects on motivation to drink should incorporate a placebo control [5]. If the study is interested in understanding motivation to drink within more 'real world' contexts, where arguably both pharmacological and expectancy effects influence drinking behaviour [89], a soft drink control would be more appropriate. A small number of studies have included an 'alcohol naïve' condition, in which participants are given alcohol, but told soft drink (this is part of the complete 'balanced placebo design') [42,70].…”
Section: Discussionmentioning
confidence: 99%